Pulse oximeters in Zaporizhzhia pharmacies - Brytanova, T. S.; Samko, A. V.; Antypenko, L.; Британова, Тетяна Сергіївна; Самко, Анатолій Васильович (My University, 2021)
Nowadays, with the increasing number of COVID-19 cases, the focus is centered on monitoring the respiratory system, which is largely due to the ubiquitous usage of pulse oximeters for remote and self-monitoring. Thus, it was decided to study their available models presented on the websites Tabletki.ua and Liki.com of Zaporizhzhia (Ukraine).
Keywords: pulse oximeters; Zaporizhzhia pharmaceutical market; COVID-19